2004
DOI: 10.1073/pnas.0404538101
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a Baeyer–Villiger monooxygenase

Abstract: Flavin-containing Baeyer-Villiger monooxygenases employ NADPH and molecular oxygen to catalyze the insertion of an oxygen atom into a carbon-carbon bond of a carbonylic substrate. These enzymes can potentially be exploited in a variety of biocatalytic applications given the wide use of Baeyer-Villiger reactions in synthetic organic chemistry. The catalytic activity of these enzymes involves the formation of two crucial intermediates: a flavin peroxide generated by the reaction of the reduced flavin with molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
305
2
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(337 citation statements)
references
References 39 publications
9
305
2
11
Order By: Relevance
“…This difference may explain why NADPH was not observed in the structure of BVMO when cocrystallized with NADPH (16). Structural differences in the substrate-binding channel almost certainly explain the difference in substrate selectivity of these enzymes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This difference may explain why NADPH was not observed in the structure of BVMO when cocrystallized with NADPH (16). Structural differences in the substrate-binding channel almost certainly explain the difference in substrate selectivity of these enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…FMO has two well defined structural domains, whereas the others have three. The BVMO structure has two structural domains within the insertion in addition to the large domain (16). Other oxidoreductases, such as NADH peroxidase and lipoamide dehydrogenase, have one small insertion domain and two domains, whereas FMO and BVMO have only one domain (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…An accurate comparison between C 2 and these structural homologs reveals that the main differences are restricted to the loops lining the flavin-and substrate-binding sites. The folding topology of C 2 is unrelated to that exhibited by other flavin-dependent monooxygenases/hydroxylases of known three-dimensional structure, such as p-hydroxybenzoate hydroxylase (15), yeast flavin-containing monooxygenase (16), and phenylacetone monooxygenase (17).…”
Section: Resultsmentioning
confidence: 96%
“…Because structural features that are unique to FMO, and yet define FMO as a family, are least amenable to modeling a priori, crystallization of an FMO remains essential to gaining an in-depth understanding of the structure and function of this family. The only bacterial flavin monooxygenase whose crystal structure has been solved is phenylacetone monooxygenase (PAMO; Malito et al, 2004). The authors found significant homology with human GR (ca.…”
Section: Poulsen and Ziegler Model Predictions For Protein Structure mentioning
confidence: 99%